Balance Strategy Combinasi Tandem Walking Exercise Efektif untuk Meningkatkan Keseimbangan Dinamis dan Kekuatan Otot Lansia - Erwin, Erwin; Katmini, Katmini; Peristiowati, Yuli; Indasah, Indasah (Jurnal Penelitian Kesehatan SUARA FORIKES, 2022)
The problem that occurs in the elderly is a balance disorder. The purpose of this study was to analyze the effectiveness of the balance strategy combined with tandem walking exercise on changes in dynamic balance and muscle strength in the elderly. Balance strategy exercise is a form of balance training based on individual strategy or ability to control the body's center of mass, so as to maintain balance. The measurement tool used for muscle strength is the thirty second chair stand test. The results of the analysis show a decrease in the mean TUG value with a value of p = 0.061, which means that there is a significant change in balance with the combination of tandem walking exercise balance strategy. While the analysis of the 30sCST value shows a value of p = 0.00, which means that there is a significant change in muscle strength in the elderly by providing a balanced strategy combination of tandem walking exercise. It was concluded that the balance strategy combination of tandem walking exercise can improve dynamic balance and muscle strength in the elderly at the Pelita Hati Elderly Social Welfare Institution, Sigi District.Keywords: balanced strategy; tandem walking exercise; dynamic balance: muscle strength ABSTRAK Permasalahan yang terjadi pada lansia adalah gangguan keseimbangan. Tujuan dari penelitian ini adalah untuk menganalisis efektifitas balance strategy kombinasi tandem walking exercise terhadap perubahan keseimbangan dinamis dan kekuatan otot pada lansia. Balance strategy exercise adalah bentuk latihan keseimbangan yang didasarkan pada strategi atau kemampuan individu dalam mengendalikan pusat massa tubuhnya, sehingga mampu mempertahankan keseimbangannya. Alat ukur yang digunakan untuk kekuatan otot adalah thirty second chair stand test. Hasil analisis menunjukkan penurunan nilai mean TUG dengan nilai p = 0,061, yang berarti bahwa terjadi perubahan secara signifikan mengenai keseimbangan dengan pemberian balance strategy kombinasi tandem walking exercise. Sedangkan analisis nilai 30sCST menunjukkan nilai p = 0,00, yang memberikan arti bahwa terjadi perubahan secara signifikan mengenai kekuatan otot pada lansia dengan pemberian balance strategy kombinasi tandem walking exercise. Disimpulkan bahwa balance strategy kombinasi tandem walking exercise dapat meningkatkan keseimbangan dinamis dan kekuatan otot pada lansia di Lembaga Kesejahteraan Sosial lanjut usia Pelita Hati Kabupaten Sigi.Kata kunci: balance strategy; tandem walking exercise; keseimbangan dinamis: kekuatan otot